Metode PI 3 Saja: Menjadi Sahabat Bagi Siapa Saja dalam Penginjilan Kontekstual di Tengah Masyarakat Non kristen, Khususnya Kota Makassar - Iswan Garamba; Ronaully Marbun (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was conducted in a Christian ministry institution located in Makassar City, South Sulawesi. The Student Creativity Program (PKM) was motivated by the reality that many people in Makassar have not yet known or believed in Isa Al-Masih (Jesus Christ )as Lord and Savior. As a city with a predominantly non-Christian population, evangelism in Makassar needs to be carried out contextually, wisely, and lovingly, without offending the beliefs of the surrounding community. The “PI 3 Saja” method (an acronym for Evangelism anytime, anywhere, and to anyone) serves as a relevant and effective strategy for reaching out to society. Through the 5P approach (Pertalian—Relationship, Peralihan—Transition, Penginsafan—Conviction, Pengabaran—Proclamation, and Penyelesaian—Commitment), this method emphasizes the importance of friendship, empathy, and naturally sharing the Gospel in everyday conversations. The purpose of this activity was to train participants in the institution to become contextual evangelists who can share the Good News without coercion, but rather through exemplary living and genuine friendship with others. The training and field practice results showed positive responses from the community, the formation of small discipleship groups (house churches), and an increased sense of courage and sensitivity among participants in sharing the Gospel in non-Christian environments. This activity demonstrates that evangelism can remain relevant and effective when it prioritizes love, relationships, and sensitivity to local culture.